(untitled) (diségno, 2023)
Exactly ten years ago, the Pinksummer gallery in Genoa hosted an exhibition in the Cortile Maggiore of the Palazzo Ducale in which two architects’ collectives, Gruppo A12 and Baukuh, questioned the possible future (or perhaps, more appropriately, the possible futures) of the Ligurian capital. And they did so by proposing projects and solutions that synergistically contaminated representational modes as varied as they were unusual: starting with the image chosen for the communication, namely that same angel, present in the Ribaudo family chapel of the Monumental Cemetery of Staglieno, used by the rock band Joy Division for the cover of its single Love will tear us apart. [read more]